Manggarai Speech Community Local Wisdom in Ireng Neka Dur Ata: Preliminary Study of Cultural Ingistics - Sakura, Katarina Noviming (Journal of A Sustainable Global South, 2019)
This article aims at describing the local wisdom of Manggarai Speech Community through a form of taboo language called ireng. Ireng is a verbal tradition contains a set of taboo actions that will bring bad luck to those who decide not to obey it. Ireng neka dur ata is the data used on this article. The local wisdom is found through analysis process of value and meaning of ireng neka dur ata. The result shows 5 facts: (1) this ireng contains of lingual unit that are modus of speech, verb choice, and word order, (2) harmony of life is the value taught through this ireng, (3) contextual meaning of this ireng is “do not extrude guest and its consequence of bad luck in economic”, (4) the local wisdom found are a habit and a sacrifice of the guest and the host, (5) the obedient to its culture, the effort maintain harmony of life, and serve people above self are reflection of the character of Manggarai Speech Community Index Terms — local wisdom, ireng, cultural linguistics